Composition operators on de Branges-Rovnyak spaces - Ghada Nasser; Abdallah Hakawati; Muath Karaki (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
We obtain invariant de Branges--Rovnyak spaces for the composition operator. We also find the images of the composition operators on the de Branges-Rovnyak spaces, for special cases of b